2011
DOI: 10.1111/j.1600-0560.2011.01812.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary cutaneous amyloidosis of the external ear: a clinicopathological and immunohistochemical study of 17 cases

Abstract: Primary cutaneous amyloidosis includes several forms of localized amyloidosis characterized by superficial amyloid deposits occurring at or near the dermal-epidermal junction in the absence of systemic involvement. Primary cutaneous amyloidosis of the auricular concha and external ear represents a rarely described variant. There have been 27 cases reported in the English language literature, and herein we report 17 additional cases. This article demonstrates that the amyloid observed in this context is general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
32
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 19 publications
0
32
0
Order By: Relevance
“…The immunohistochemical results suggested that the amyloid deposits in these cases may be a result of basal keratinocyte degeneration and do not signify deposition from a systemic or generalized process. [17] The diagnosis of the condition requires a high index of suspicion and one should consider the diagnosis in middle-aged females presenting with long standing, hyperpigmented, multiple, hyperkeratotic, papules involving bilateral conchal bowls, crura of the antihelices, or external auditory canals. The papules range in size from 1-2 mm in diameter, are firm and discrete but may coalesce in areas to resemble plaques.…”
Section: Discussionmentioning
confidence: 99%
“…The immunohistochemical results suggested that the amyloid deposits in these cases may be a result of basal keratinocyte degeneration and do not signify deposition from a systemic or generalized process. [17] The diagnosis of the condition requires a high index of suspicion and one should consider the diagnosis in middle-aged females presenting with long standing, hyperpigmented, multiple, hyperkeratotic, papules involving bilateral conchal bowls, crura of the antihelices, or external auditory canals. The papules range in size from 1-2 mm in diameter, are firm and discrete but may coalesce in areas to resemble plaques.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there is a report that presented a patient with subaural arteriovenous malformation complicated by macrotia 4 . Further, some rheumatological diseases such as sarcoidosis and amyloidosis should be included in the differential diagnosis of acquired external ear deformities because of their various manifestations, which may involve the external ear 5,19 .…”
Section: Discussionmentioning
confidence: 99%
“…The first case reports suggest a collagenous nature of the material, as they were stained with Verhoeff-van Gieson and Periodic acid-Schiff (PAS) and not with Congo red, and presented electronic microscopy consistent with collagen deposit, and the lesions were called collagen papules of the auricular concha. 4 However, the majority of the reported cases demonstrated that the material was stained with Crystal Violet and became orange-colored with Congo red, generally presenting positive birefringence when submitted to polarized light, thus suggesting the amyloid origin of such deposits. 1,2,3,4 According to the author of the largest case study on this issue, they could represent two distinct entities, though clinically similar, which could have been clarified if immunohistochemistry had been used in the first cases.…”
mentioning
confidence: 98%
“…These papules are generally asymptomatic, however, in some cases, they can be pruritic. 4 Differential diagnoses include seborrheic keratosis, viral warts, calluses, basal-cell carcinoma, adnexal neoplasms, and chronic erythematous lupus. 4 There is no consensus if this condition is in fact a new subtype of primary cutaneous amyloidosis or a variant of lichen amyloidosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation